Pengaruh Semangat Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan Sekolah Kedokteran Hewan dan Biomedis IPB University - Fajar Fahrudin; Popy Novita Pasaribu; Hannisa Rahmaniar Hasnin (CV. ITTC INDONESIA, 2026)
Employee performance is an important factor in determining organizational success in achieving its objectives. Performance improvement is influenced by several internal factors, including work spirit and organizational commitment. This study aims to analyze the effect of work spirit and organizational commitment on employee performance at the School of Veterinary Medicine and Biomedical Sciences (SKHB) IPB University, both partially and simultaneously. This research employed a quantitative approach using an associative method. The population consisted of all employees of SKHB IPB University, with 76 respondents selected using a saturated sampling technique. Data were collected through questionnaires using a Likert scale. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination using IBM SPSS Statistics version 25. The findings indicate that work spirit has a positive and significant effect on employee performance with a significance value of 0.000 and a t-value of 8.433. Organizational commitment also has a positive and significant effect on employee performance with a significance value of 0.000 and a t-value of 3.983. Simultaneously, both variables significantly influence employee performance with an F-value of 93.937 and a significance value of 0.000. The Adjusted R Square value of 0.713 indicates that work spirit and organizational commitment explain 71.3% of the variance in employee performance